Back Analysis of Static Lateral Loading Tests of Pile Foundations in Soft Soils - Miranti, Miranti; Prakoso, Widjojo Adi (Universitas Ibn Khaldun Bogor, 2024)
Pile foundations are used to support structures. In addition to bearing the pile's load, the design's foundation structure must withstand lateral loads. As a result of the pile being exposed to lateral loads, it causes deflection or displacement of the pile. One method of testing foundation capacity is the static lateral loading test. The result of this test is the lateral deflection of the pile, with a certain load given to the pile head due to cyclic loads. The lateral loading test data in the study was tested on seven piles with a diameter of 600 m at the Kapuk Banten project site. The soil investigation results found that the dominance of soft clay soil is quite thick. This research aims to back-analyze the results of static lateral loading tests using LPile 2019 software as a model evaluation in soft soil geotechnical conditions. The back analysis obtained soil parameters that produced deflections close to the results of static lateral loading tests.